Folic acid, one-carbon metabolism, MTHFR polymorphisms and pathologies - Sambo, Patrícia Muíla Bragança (2014)
The interaction between folate and methylenetetrahydrofolate reductase (MTHFR) gene is an example of a strong gene-nutrient interaction. MTHFR 677C→T polymorphism may be associated with homocysteine in the modulation of the cardiovascular disease (CVD). Additionally, the interaction between the polymorphism and folate has been linked to a protective effect in individuals with colorectal cancer (CRC). The aim of this work is to assess the possible association between MTHFR 677C→T polymorphism, CVD and CRC, modified by folate and homocysteine. The predictive response of CRC patients carrying MTHFR 677C→T polymorphism, treated with 5-fluorouracil, is also briefly examined, along with the current strategies to inhibit tumours, involving MTHFR gene as a target. Studies were found by searches of electronic literature for papers up to October 2014 using the terms “MTHFR 677C→T polymorphism” “folate,” “cardiovascular disease,” “homocysteine,” “colorectal cancer” and “chemotherapy”. Collected studies were mainly observational, randomised controlled trials, meta-analyses and systematic reviews, approximately from the last 15 years. The association between MTHFR 677C→T polymorphism and CVD was found, although results from folate supplementation trials demonstrated no benefit in CVD. High supply of folate and TT genotype carriers may have a lower risk to develop colon cancer in some populations. The type and amount of folate, along with its supplementation when carcinogenesis is already stablished may increase the risk for CRC. MTHFR 677C→T polymorphism seems to be associated with better prognosis and less toxicity in 5-fluorouracil monotherapy. MTHFR inhibition technique shows promising results as an anti-cancer therapy. Findings are inconsistent to recommend folate supplementation in TT genotype carriers with CVD and CRC. A genetic and environmental risk assessment for CRC risk in primary care, regarding folate and MTHFR 677C→T polymorphism is worth considering. Further research on combinatory MTHFR polymorphisms and riboflavin effect, could help clarify the association between MTHFR 677C→T polymorphism, folate and disease.